New combination of xylanolytic bacteria isolated from the lignocellulose degradation microbial consortium XDC-2 with enhanced xylanase activity. (December 2016) - Zhang, Dongdong; Wang, Yi; Zheng, Dan; Guo, Peng; Cheng, Wei; Cui, Zongjun
Graphical abstract: Highlights: An aerobic xylanolytic strain was combined with anaerobic xylanolytic strains. Xylanase activity was enhanced by combining Bacillus sp. and Clostridium sp. Not all xylanolytic bacterium can coexist with xylanase production enhancement. Bacillus sp. enabled the growth of anaerobic Clostridium sp., not Bacteroides sp. Abstract: Three bacterial strains with extracellular xylanase activity were isolated from the microbial consortium XDC-2. The aerobic strain A7, belonging to Bacillus sp., was combined with the anaerobe Clostridium sp. strain AA3 and/or Bacteroides sp. strain AA4 to obtain an efficient natural xylanolytic complex enzyme. The synthetic microbial community M1 consisting of strains Bacillus and Clostridium showed enhanced extracellular xylanase activity and production, and higher lignocelluloses degradation capability than any of the pure cultures and other synthetic microbial communities. Neither corn straw degradation nor extracellular xylanase activity was enhanced in the other synthetic microbial communities, Bacillus, Bacteroides with or without Clostridium . Quantitative polymerase chain reaction showed that the aerobic strain Bacillus enabled the growth of the anaerobic strain Clostridium, but not that of the anaerobic strain Bacteroides . These findings suggest that strains Bacillus and Clostridium can coexist well and have a positive synergistic interaction for extracellular xylanase secretion and lignocellulose degradation.